2011
DOI: 10.1017/s0144686x10001340
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing computer self-efficacy and attitudes in multi-ethnic older adults: a randomised controlled study

Abstract: Several studies have documented the health-related benefits of older adults' use of computer technology, but before they can be realised, older individuals must be positively inclined and confident in their ability to engage in computer-based environments. To facilitate the assessment of computer technology attitudes, one aim of the longitudinal study reported in this paper was to test and refine a new 22-item measure of computer technology attitudes designed specifically for older adults, as none such were av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 39 publications
2
22
0
8
Order By: Relevance
“…59 If health is a reason for a decline in mastery, a focus should be on establishing how the Internet might provide support so as to counteract a decline in sense of mastery. Conversely, studies have indicated that not knowing how to use the Internet well can be stressor in itself for an older adult, 10,60 which could trigger a decline in mastery.…”
Section: Discussionmentioning
confidence: 99%
“…59 If health is a reason for a decline in mastery, a focus should be on establishing how the Internet might provide support so as to counteract a decline in sense of mastery. Conversely, studies have indicated that not knowing how to use the Internet well can be stressor in itself for an older adult, 10,60 which could trigger a decline in mastery.…”
Section: Discussionmentioning
confidence: 99%
“…Senior Citizens' Attitudes toward Computers (SAC) . To measure seniors' attitudes toward computers and toward learning basic computer skills, a specific scale was designed based on instruments used and validated in previous research on this subject (see the Appendix) [ 23 25 ]. With the aim of measuring these attitudes, various items used by these instruments were considered and adapted to the population participating in the study, which generally had a low level of education and little or no prior computer contact.…”
Section: Methodsmentioning
confidence: 99%
“…Older adults are capable of learning new technologies (Hickman, Rogers and Fisk 2007), although this may involve additional practice and support (Nair, Czaja and Sharit 2007). Older adults felt less anxious about ICTs after training (Irizarry, Downing and West 2002; Xie and Bugg 2009), saw potential advantages and uses of the technology (Campbell 2004), and reported increased interest in computer use and efficacy and improved attitudes toward computer technology (Laganá et al 2011; Xie and Bugg 2009). Mastery of new skills lets older adults keep in closer contact with family and friends (Namazi and McClintic 2003), and keeps them up-to-date in the modern world (Clark and Straka 2000).…”
Section: Literature Reviewmentioning
confidence: 99%